Components and Characteristics of the Professional Competency Model among Educational Administrators - Astereki, Samaneh (2021)
Education is the most basic institution in the development process in each country. In other words, if education is dynamic, active, and vibrant in a country, the country will naturally be a growing and developed country. Professional and effective training of professional and effective managers is one of the basic problems, whose successful and effective implementation in an organization requires a set of competencies, skills, abilities, and special characteristics. Competence is a special tool for workforce planning and management. In this regard, much attention to the competency approach stems from the capabilities of the organization. In other words, a successful and effective organization creates and maintains its competitive advantage by developing individuals’ competencies. On the other hand, the competency approach is of great importance in the development of managers as they can develop and improve their performance by adopting such an approach. Accordingly, the present study aimed to investigate the components and characteristics of the professional competency model among educational administrators. The study findings revealed that the most prominent management dimension encompasses supervision and guidance, knowledge management, evaluation, decision-making, and planning. Personality dimension includes ethics, creativity and innovation, communication skills, and negotiation skills. Technological dimension consists of information literacy, application of new technologies in teaching, the use of information and communication technology, and the ability to work in a virtual environment. Educational-research dimension addresses research orientation, applied scientific research, familiarity with teaching methods and techniques, and incentives for employees to teach effectively. This descriptive-analytical study adopted a library technique.